Preparation and application of multifunctional electroluminescent materials with AIE properties and reversible mechanochromic properties

By designing D-π-A type organic small molecule electroluminescent material and combining the twisted structure of the multi-ring rotor, the problems of complex operation and extended conversion time of existing AIE mechanical color discoloration materials are solved, and efficient and reversible mechanical color discoloration effect is achieved, with wide application potential.

CN119080696BActive Publication Date: 2025-05-02HAINAN NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411190980.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-05-02
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing mechanical color-changing materials with AIE characteristics have problems such as complex operation and extended conversion time in actual applications, which hinder their wide application.

Method used

A D-π-A type organic small molecule electroluminescent material was designed. By connecting the halogen chromatic group isoquinoline and the mechanical chromatic group t-BuTPA as a π bridge, forming a donor-π bridge-acceptor structure, combining the twisted structure of the multi-ring rotor, the AIE properties and reversible mechanical discolorability of the material are realized.

Benefits of technology

This material not only exhibits excellent AIE characteristics, but also exhibits reversible, machining and high-contrast mechanical discoloration. It has a simple preparation method and mild reaction conditions, making it suitable for promotion and production applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080696B_ABST
    Figure CN119080696B_ABST
Patent Text Reader

Abstract

The invention discloses the preparation and application of a multifunctional electroluminescent material with AIE properties and reversible mechanical color-changing properties, and belongs to the field of organic small molecule electroluminescent materials. The preparation method of the D-π-A type organic small molecule electroluminescent material of the present invention comprises the following steps: mixing tBu-TPA with dibrominated naphthalene, coupling reaction, and obtaining intermediate 1; mixing the intermediate 1 with biboric acid pinacol ester, boronization reaction, and obtaining intermediate 2; mixing the intermediate 2 with 1-bromoisoquinoline, and performing Suzuki coupling reaction to obtain the D-π-A type organic small molecule electroluminescent material. The product of the present invention not only exhibits excellent AIE properties, but also exhibits reversible, processable and high-contrast mechanical color change. Based on the twisted structure of the multi-ring rotor, the electroluminescent material of the present invention shows obvious fluorescent color, which changes significantly during mechanical grinding, and the process of mechanical color change is reversible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic small molecule electroluminescent materials, and in particular to the preparation and application of a multifunctional electroluminescent material with AIE properties and reversible mechanochromic properties. Background Art

[0002] Electroluminescent materials can be divided into inorganic materials and organic materials according to their material composition; inorganic luminescent materials include rare earth metal complex materials and alkaline earth metal materials, while organic luminescent materials include small molecules, transition metal complex polymers, etc. Organic small molecule luminescent materials have been widely studied and applied due to their simple structure, reproducibility and easy purification. Some functional organic small molecule luminescent materials show color rendering and stimulus responsiveness, and can adjust their chemical or physical properties when exposed to external stimuli. Smart fluorescent materials show reversible fluorescence changes when exposed to external stimuli (such as heat, pressure, light, solvent vapor and pH value). Among them, mechanochromic fluorescent materials have attracted widespread attention due to their ability to reversibly change their apparent color, emission wavelength or intensity under different mechanical effects. These materials are widely used in mechanical sensing and security inks. The planar structure of traditional luminescent materials is prone to aggregation-induced quenching (ACQ) effect, resulting in weak mechanical luminescence and low contrast in the aggregated state, which seriously hinders their practical application. This reduction in efficiency is mainly caused by the π-π stacking of molecules and the formation of exciplexes, which leads to the non-radiative deactivation of excited-state energy.

[0003] Recent studies have found that some propeller-shaped molecules exhibit an effect directly opposite to the ACQ effect, which emits weak light in solution but emits strong fluorescence in the condensed state. This photophysical phenomenon is called aggregation-induced emission (AIE). The effective use of AIE luminogens (AIEgens) in solid-state emission has been demonstrated to be a successful strategy to overcome the ACQ effect and exciton quenching in electroluminescent devices. Given their outstanding properties, AIEgens have great potential as efficient emitters for organic light-emitting devices (OLEDs) with high-efficiency luminescence and low-efficiency decay. So far, an increasing number of AIE materials exhibiting mechanochromic properties have been developed and applied in various fields, including pressure sensors, information security and storage, optoelectronic devices, and wearable systems. However, current mechanochromic materials with AIE properties still have disadvantages such as complex operation or prolonged switching time, which hinders practical applications. Summary of the invention

[0004] The object of the present invention is to provide a preparation and application of a multifunctional electroluminescent material having AIE properties and reversible mechanochromic properties to solve the above-mentioned problems in the background technology. The product of the present invention not only exhibits excellent AIE properties, but also exhibits reversible, processable and high-contrast mechanochromic properties. Based on the twisted structure of the multi-ring rotor, the electroluminescent material of the present invention exhibits obvious fluorescent color, which changes significantly during mechanical grinding, and the process of mechanochromic change is reversible.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a D-π-A type organic small molecule electroluminescent material, the general structural formula of the D-π-A type organic small molecule electroluminescent material is as follows:

[0007]

[0008] Wherein, X is

[0009] The second technical solution of the present invention is to provide a method for preparing the above-mentioned D-π-A type organic small molecule electroluminescent material, comprising the following steps:

[0010] Mix tBu-TPA and dibromonaphthalene and perform coupling reaction to obtain intermediate 1;

[0011] The intermediate 1 is mixed with biboric acid pinacol ester, and subjected to borylation reaction to obtain the intermediate 2;

[0012] The intermediate 2 and 1-bromoisoquinoline are mixed and subjected to a Suzuki coupling reaction to obtain the D-π-A type organic small molecule electroluminescent material;

[0013] The structural formula of the tBu-TPA is shown below:

[0014]

[0015] The dibrominated naphthalene is 1,4-dibromonaphthalene or 2,6-dibromonaphthalene.

[0016] Preferably, the molar ratio of tBu-TPA to dibromonaphthalene is 1.9-2:3.9-4.

[0017] Preferably, the coupling reaction is carried out at a temperature of 80° C., for a time of 6 hours, in an oxygen-free atmosphere.

[0018] Preferably, the molar ratio of the intermediate 1 to the diboric acid pinacol ester is 2:3.

[0019] Preferably, the temperature of the borylation reaction is 110° C., the time is 24 hours, and the atmosphere is an oxygen-free atmosphere.

[0020] Preferably, the molar ratio of the intermediate 2 to 1-bromoisoquinoline is 1-1.055:1.2-1.27.

[0021] Preferably, the temperature of the Suzuki coupling reaction is 110° C., the time is 24 h, and the atmosphere is oxygen-free.

[0022] When the dibrominated product of naphthalene is 1,4-dibromonaphthalene, the structural formulas of intermediate 1, intermediate 2 and the final product (denoted as t-BuTPAniq) are respectively:

[0023]

[0024] When the dibrominated product of naphthalene is 2,6-dibromonaphthalene, the structural formulas of intermediate 1, intermediate 2 and the final product (denoted as t-BuTPA2niq) are respectively:

[0025]

[0026] The third technical solution of the present invention is to provide an application of the above-mentioned D-π-A type organic small molecule electroluminescent material in the preparation of the light-emitting layer of an electroluminescent device.

[0027] The fourth technical solution of the present invention is to provide a method for preparing a light-emitting layer of an electroluminescent device, which is prepared by mixing the above-mentioned D-π-A type organic small molecule electroluminescent material with a host material;

[0028] The D-π-A type organic small molecule electroluminescent material accounts for 10-40 wt.% in the light-emitting layer of the electroluminescent device.

[0029] Preferably, the main material is PPF.

[0030] The present invention also discloses a method for preparing an electroluminescent device, wherein an indium tin oxide (ITO) conductive glass substrate layer is used, PPF, TAPC, TCTA and TmPyPB are used as a host material, a hole injection layer, a hole transport layer and an electron transport layer respectively, and a D-π-A type organic small molecule electroluminescent material is doped into the PPF host material as a light-emitting layer (EML).

[0031] The technical principles of the present invention are as follows:

[0032] In the organic fluorescent molecules t-BuTPAniq and t-BuTPA2niq designed by the present invention, a donor-π bridge-acceptor structure (D-π-A) is formed by connecting the halogen color group isoquinoline (IQ) and the mechanical color group t-BuTPA through naphthalene as a π bridge. The triphenylamine (TPA) donor part has a propeller structure, which can prevent π-π stacking; the introduction of the tert-butyl group increases the non-planarity of the molecule, further suppresses the intermolecular stacking interaction between the planar groups, makes the internal structure of the organic small molecule luminescent group less compact, and is more sensitive to external stimuli, thereby providing multi-color solid-state luminescence in the mechanical fluorescence process.

[0033] The organic small molecule compound of the present invention is processed by solution and used as a luminescent material (guest material) to be doped with a host material to prepare a luminescent layer. It can be applied to a single-luminescent-layer organic small molecule electroluminescent device and has good conversion efficiency.

[0034] The beneficial technical effects of the present invention are as follows:

[0035] The present invention discloses a multifunctional organic small molecule electroluminescent material with aggregation-induced (AIE) properties and reversible mechanochromic properties. In the D-π-A type molecule of the present invention, the restricted rotation of the donor and acceptor electrons around the π connector contributes to the performance of the AIE effect, and by increasing the transition energy between the molecular ground state and the excited state, the band gap energy is improved, and the π bridge in the HOMO distribution is more conducive to maximizing the radiation transition rate in the dominant emission between electron transfers through effective electronic coupling with the charge transfer internal state, and the fluorescence efficiency is higher than that of the DA type molecule. At the same time, the introduction of the π bridge can further improve the horizontal emission dipole orientation ratio and optical decoupling efficiency of OLEDs. The product of the present invention not only exhibits excellent AIE characteristics, but also exhibits reversible, processable and high-contrast mechanochromic properties. Based on the twisted structure of the multi-ring rotor, the electroluminescent material of the present invention shows obvious fluorescent color, which changes significantly during mechanical grinding, and the process of mechanochromic is reversible.

[0036] The preparation method of the invention is simple and has mild reaction conditions, which is conducive to popularization of production and application.

[0037] The present invention combines reversible, processable and high-contrast mechanical dyeability in a single molecule, and has acidochromic properties. By utilizing the mechanical and acidochromic properties, it can be applied to the field of fluorescent anti-counterfeiting, and has great application potential in display, lighting technology and the like.

[0038] In the present invention, the organic electroluminescent device prepared by the organic small molecule electroluminescent material exhibits excellent performance. Specifically, the organic light-emitting devices (OLEDs) prepared by using t-BuTPAniq and t-BuTPA2niq respectively achieve maximum EQEs of 4.0% and 3.6%, and the emission peak is at 472nm. The organic small molecule electroluminescent material of the present invention has a good application value in the development of multifunctional blue electroluminescent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 The UV-visible absorption spectra of the products of Examples 1-2 in different solutions are shown in Figure 1, where (a) is Example 1 and (b) is Example 2.

[0041] Figure 2 The fluorescence emission spectra of the products of Examples 1-2 in different solutions are shown in Figure 1. (a) is Example 1, and (b) is Example 2.

[0042] Figure 3 The fluorescence emission spectra of the products of Examples 1-2 in methanol / water mixtures with different water volume fractions are shown in Figure 1. (a) is Example 1, and (b) is Example 2.

[0043] Figure 4 The fluorescence emission spectra and fluorescence modified digital images of the products of Examples 1-2 by mechanical color change are shown in Figure 1, where (a) is Example 1 and (b) is Example 2.

[0044] Figure 5 The fluorescence emission spectra and fluorescence modified digital images of the products of Examples 1-2 after fumigation with hydrochloric acid and ammonia, wherein (a) is Example 1 and (b) is Example 2.

[0045] Figure 6 The following are simulation diagrams of the effects of the products of Examples 1-2 in the field of fluorescent anti-counterfeiting, wherein (a) is Example 1 and (b) is Example 2.

[0046] Figure 7 The radiation intensity diagram of the PPF electroluminescent device doped with the product of Example 1-2, wherein (a) is Example 1, and (b) is Example 2.

[0047] Figure 8The external quantum efficiency curves of the PPF electroluminescent device doped with the product of Example 1-2 are shown in FIG.

[0048] Fig. 9 The electroluminescence spectra of the PPF electroluminescent device doped with the product of Example 1-2 are shown in Figure 1, where (a) is Example 1 and (b) is Example 2. DETAILED DESCRIPTION

[0049] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0050] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0051] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0052] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0053] The "room temperature" in the present invention is 10-30°C unless otherwise specified.

[0054] The reaction formula of the present invention when preparing the product of Example 1-2 is shown below (the number 1-5 in the reaction formula corresponds to the intermediate 1-5 in Example 1-2):

[0055]

[0056] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0057] Example 1

[0058] A method for preparing a D-π-A type organic small molecule (t-BuTPAniq), comprising the following steps:

[0059] (1) Preparation of Intermediate 2: In a 100 mL double-necked flask, 4-tert-butyl-N-(4-tert-butyl)phenyl-N-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl)aniline (Intermediate 1) (0.942 g, 1.9 mmol), 1,4-dibromonaphthalene (1.107 g, 3.9 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 ) (87.8 mg, 0.08 mmol), 10 mL potassium carbonate solution (1 mol / L), 10 mL methanol and 50 mL toluene. 2 Under protection, the reaction was stirred at 80°C for 6 hours, the reaction was stopped, and the reaction was cooled to room temperature. Toluene and methanol in the system were removed, and the mixture was extracted with water and dichloromethane (3×30 mL) 3 times. The organic phases were combined and dried over anhydrous magnesium sulfate for 6 hours and filtered. The crude product was separated by silica gel column chromatography using 150:1 (V / V) petroleum ether and dichloromethane as eluents to obtain intermediate 2 (0.646 g, yield 60.60%) (4-(4-bromonaphthalene-1-ethyl)-N, N-di(4-(tert-butyl)phenyl)aniline) as a white solid.

[0060] 1H NMR (400MHz, CDCl 3 )δ8.32(d,J=8.1Hz,1H),8.03(d,J=8.2Hz,1H),7.82(d,J=7.7Hz,1H),7.61(t,J=7.6Hz,1H) ,7.51(t,J=7.0Hz,1H),7.33-7.27(m,7H),7.14(dd,J=13.1,8.6Hz,6H),1.34(s,18H).HRMS calce for C 36 H 36 BrN[M+Na-H] + 583.2479 found 583.2432.

[0061] (2) Preparation of intermediate 4: In a 100 mL double-necked bottle, add intermediate 2 (1.251 g, 2.2 mmol), 0.849 g (3.3 mmol) of biphenylboric acid pinacol ester, 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride (Pd(dppf) 2 Cl 2 ) (0.0981 g, 0.1 mmol), potassium acetate (KOAc) (0.546 g, 5.6 mmol) and 50 mL of 1,4-dioxane solution. 2Under protection, the reaction was stirred at 110 ° C for 24 hours, the reaction was stopped and cooled to room temperature. After removing the 1,4-dioxane solution in the system, it was extracted with water and dichloromethane (3×30mL) 3 times, the organic phases were combined and dried over anhydrous magnesium sulfate for 6 hours, and filtered. The crude product was separated by silica gel column chromatography using 5:1 (V / V) petroleum ether and dichloromethane as eluents to obtain intermediate 4 (0.983g, yield 72.38%) (4-(tert-butyl)-N-(4-(tert-butyl)phenyl)-N-(4-(4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)naphthalene-1-yl)phenyl)aniline) as a white solid.

[0062] 1H NMR (400MHz, CDCl 3 )δ8.02(dd,J=23.7,8.5Hz,1H),7.64(d,J=7.1Hz,1H),7.46(d,J=8.3Hz,1H),7.39(t,J=7.1Hz,1H),7.28( d,J=2.5Hz,1H),7.25-7.18(m,7H),7.10-6.99(m,6H),1.26(d,J=2.1Hz,18H),1.22(d,J=3.2Hz,12H).[M] + 609.3378 found 609.3365.

[0063] (3) Preparation of t-BuTPAniq: In a 100 mL double-necked flask, intermediate 4 (0.590 g, 1.055 mmol), 1-chloroisoquinoline (0.206 g, 1.27 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh 3)4 ) (0.0610 g, 0.0528 mmol), 3.90 mL potassium carbonate solution (1 mol / L), 10 mL methanol and 50 mL toluene. 2 Under protection, stir at 110 ° C for 24 hours, stop the reaction, and cool to room temperature. After removing toluene and methanol in the system, extract with water and dichloromethane (3×30mL) 3 times, combine the organic phases and dry with anhydrous magnesium sulfate for 6 hours, and filter. The crude product is separated by silica gel column chromatography using 10:1 (V / V) petroleum ether and ethyl acetate as eluents. t-BuTPAniq (0.2701g, yield 45.69%) is obtained as a yellow solid.

[0064] 1H NMR (400MHz, CDCl 3)δ8.70(d,J=5.7Hz,1H),8.12(d,J=9.1Hz,1H),7.93(d,J=8.3Hz,1H),7.76-7.66(m,3H),7.58(dd,J=16.8,7.2 HRMS calceforC 45 H 42 N 2 [M+H] + 611.3421 found 611.3434.

[0065] Example 2

[0066] A method for preparing a D-π-A type organic small molecule (t-BuTPA2niq), the steps are as follows:

[0067] (1) Preparation of Intermediate 3: The only difference from step (1) in Example 1 is that 1,4-dibromonaphthalene is replaced by an equal molar amount of 2,6-dibromonaphthalene to obtain Intermediate 3 (0.513 g, yield 48.12%) as a white solid.

[0068] 1H NMR (400MHz, CDCl 3 )δ7.96(d,J=18.5Hz,2H),7.76-7.69(m,2H),7.58-7.51(m,3H),7.46-7.38(m,1H),7 .31-7.26(m,4H),7.17-7.12(m,2H),7.10-7.05(m,4H),1.33(d,J=3.0Hz,18H).HRMS calce for C 36 H 36 BrN[M+Na-H] + 583.2479 found 583.2426.

[0069] (2) Preparation of Intermediate 5: The only difference from step (2) in Example 1 is that Intermediate 2 is replaced by an equimolar amount of Intermediate 3 to obtain Intermediate 5 (0.677 g, yield 49.85%) as a white solid.

[0070] 1H NMR (400MHz, CDCl 3)δ8.33(s,1H),7.95(s,1H),7.81(s,2H),7.55(d,J=8.6Hz,2H),7.32(d,J=2.5Hz,1H),7.23( d,J=7.8Hz,4H),7.12(d,J=8.5Hz,2H),7.04(d,J=8.5Hz,5H),1.36(s,12H),1.29(s,18H).[M] + 609.3378 found 609.3389.

[0071] (2) Preparation of t-BuTPA2niq: The only difference from step (2) in Example 1 is that intermediate 2 is replaced by an equimolar amount of intermediate 3 to obtain t-BuTPA2niq (0.2701 g, yield 45.69%) as a yellow solid.

[0072] 1H NMR (400MHz, CDCl3) δ8.68(d,J=5.7Hz,1H),8.21(d,J=8.7Hz,2H),8.10(s,1H),8.04(d,J =8.5Hz,1H),7.99(d,J=8.6Hz,1H),7.92(d,J=8.2Hz,1H),7.86(d,J=8.4Hz,1H),7.81(d,J =10.3Hz,1H),7.70(t,J=6.6Hz,2H),7.64(d,J=8.7Hz,2H),7.58(d,J=8.3Hz,1H),7.55(s, 1H),7.31(d,J=8.6Hz,4H),7.20(d,J=8.6Hz,2H),7.11(d,J=8.6Hz,4H),1.35(s,18H).13C NMR(101MHz,CDCl 3 )δ160.61,147.85,145.93,144.95,142.13,138.99,137.05,136.51,133.79, 132.04,130.16,129.31,128.95,128.23,127.88,127.35,127.01,126.11,125 .87,124.69,124.19,123.05,120.01,77.34,77.02,76.70,41.37,34.33,31. 53,29.07,22.92,22.48,20.44,19.44,18.77,14.31,14.11,11.42.HRMScalce for C45H42N2[M+H]+611.3421found611.3414.

[0073] The 1H NMR spectrum of the product of Example 1-2 was measured by a Bruker-400 NMR instrument.

[0074] Effect verification

[0075] Performance characterization of the product of Example 1-2 and preparation and luminescence performance testing of its single-light-emitting polymer electroluminescent device:

[0076] 1. Test Method

[0077] The UV-visible absorption spectrum of the product of Example 1-2 was measured by a U-3900 UV-visible spectrometer, and the fluorescence emission spectrum was measured by a Hitachi F-700 fluorescence spectrometer.

[0078] The single-light-emitting polymer electroluminescent device based on organic small molecule compound materials is composed of the following devices: an indium tin oxide (ITO) conductive glass substrate layer, PPF, TAPC, TCTA and TmPyPB as the host material, hole injection layer, hole transport layer and electron transport layer respectively, and organic small molecules are doped into the PPF host with different doping concentrations as the light-emitting layer (EML).

[0079] The product of Example 1-2 accounts for 10-40 wt.% in the light-emitting layer of the electroluminescent device.

[0080] The structure of the fabricated polymer electroluminescent device is as follows:

[0081] ITO / HAT-CN, (10nm) / TAPC, (40nm) / TCTA, (10nm) / PPF, (x wt%, 20nm) / TmPyPB, (40nm) / Liq (3nm) / Al (60nm).

[0082] The device fabrication procedure is as follows: -6 OLEDs were fabricated on an ITO glass substrate layer (110 nm, 15 Ω / m2) under a substrate pressure of 100 μm. The active area of ​​each device was 0.09 cm 2 The deposition rate and thickness of all materials were monitored using an oscillating quartz crystal. The doped layers were deposited using two different sensors to monitor the deposition rate of the bulk material and the dopant material. The bulk deposition rate was controlled at 0.2 nm·s -1 The deposition rate of the dopant was adjusted according to the volume ratio of the dopant in the host material. The electroluminescence (EL) and current density-voltage (JV) characteristics of the device were measured by a constant current source (Keithley 2400 Source Meter) combined with a photometer (Photo Research SpectraScan PR655).

[0083] 2. Effect Characterization

[0084] Figure 1 The UV-visible absorption spectra of the products of Examples 1-2 in different solutions are shown in Figure 1, where (a) is Example 1 and (b) is Example 2.

[0085] like Figure 1 As shown, the absorption wavelengths of the two molecules in toluene are the longest, at 352nm and 367nm, respectively. Between the aromatic amine and isoquinoline, the strong absorption at 275-325nm belongs to the intramolecular π-π* electronic transition. The broad absorption at 325-450nm is attributed to the intramolecular charge transfer (ICT) from the D unit to the A unit.

[0086] Figure 2 The fluorescence emission spectra of the products of Examples 1-2 in different solutions are shown in Figure 1. (a) is Example 1, and (b) is Example 2.

[0087] like Figure 2 As shown, the emission spectra of the two molecules in different solvents are red-shifted, proving the excited state of the natural CT component. The emission wavelengths of t-BuTPAniq and t-BuTPA2niq in dimethyl sulfoxide are the longest, at 541 nm and 553 nm, respectively.

[0088] Figure 3 The fluorescence emission spectra of the products of Examples 1-2 in methanol / water mixtures with different water volume fractions are shown in Figure 1. (a) is Example 1, and (b) is Example 2.

[0089] like Figure 3 As shown in the figure, when the water volume fraction (f w ) increased from 0 to 40%, the fluorescence intensity of t-BuTPAniq and t-BuTPA2niq hardly changed. w When the fluorescence intensity increases from 50% to 70%, it increases significantly. w The peak value was reached when t-BuTPA2niq f w When the fluorescence intensity increases from 50% to 80%, it increases significantly. w The strongest fluorescence intensity was reached at 0%, which was about 10.6 times that of 0%. This indicates that at a higher water volume fraction, these molecules begin to aggregate, and this aggregation state leads to enhanced fluorescence. This indicates that t-BuTPAniq and t-BuTPA2niq have AIE properties.

[0090] Figure 4 The fluorescence emission spectra and fluorescence modified digital images of the products of Examples 1-2 by mechanical color change are shown in Figure 1, where (a) is Example 1 and (b) is Example 2.

[0091] like Figure 4 As shown, strong grinding of t-BuTPAniq showed a red shift in fluorescence (from 437nm to 453nm), and heating reversed the fluorescence. Similarly, t-BuTPA2niq exhibited a red shift in fluorescence (from 429 to 459nm) when ground, and heating also reversed the fluorescence. For t-BuTPAniq, the present invention observed a significant increase in the molecular brightness after grinding or heating compared to the sample before grinding. In contrast, the molecular brightness of t-BuTPA2niq was significantly reduced after grinding and heating. The former may be attributed to its crystal structure, in which the π bridge rotation is fixed by intermolecular interactions, resulting in a rigid molecular structure, so the brightness becomes stronger after grinding. This mechanical color change effect can be attributed to the phase transition from crystalline to amorphous during molecular grinding. Strong grinding destroys the molecular stacking in the crystal structure and transforms the highly ordered crystalline state into a disordered amorphous phase. The transition from a highly organized state to a disordered state completely extinguishes the fluorescence associated with flat isoquinoline.

[0092] Figure 5 The fluorescence emission spectra and fluorescence modified digital images of the products of Examples 1-2 after fumigation with hydrochloric acid and ammonia, wherein (a) is Example 1 and (b) is Example 2.

[0093] like Figure 5 As shown, protonation upon exposure to hydrochloric acid vapor causes fluorescence to turn off, while exposure to ammonia turns on fluorescence. This will be beneficial for its application in the field of fluorescent anti-counterfeiting.

[0094] t-BuTPAniq and t-BuTPA2niq were dissolved in DCM, cotton swabs were soaked in t-BuTPAniq solution and t-BuTPA2niq solution respectively, and then "HNU" patterns were drawn on filter paper to test their working performance in the field of fluorescent anti-counterfeiting.

[0095] Figure 6 The following are simulation diagrams of the effects of the products of Examples 1-2 in the field of fluorescent anti-counterfeiting, wherein (a) is Example 1 and (b) is Example 2.

[0096] like Figure 6 As shown in the figure, the drawn pattern is reduced after being fume-generated by hydrochloric acid vapor in sunlight, and the fluorescence of t-BuTPAniq and t-BuTPA2niq is restored to the initial state after being gassed by ammonia vapor. This effect provides a basis for designing fluorescent anti-counterfeiting technologies with different performances.

[0097] Figure 7 The radiation intensity diagram of the PPF electroluminescent device doped with the product of Example 1-2, wherein (a) is Example 1, and (b) is Example 2.

[0098] like Figure 7As shown. The turn-on voltage (Von) is 5.8 V for t-BuTPAniq and 8.7 V for t-BuTPA2niq, indicating efficient charge injection and recombination in the EML. The lower driving voltage of the device based on t-BuTPAniq is mainly due to the better carrier mobility of the t-BuTPAniq film. Since the HOMO / LUMO of t-BuTPAniq and tBu-TPA2niq are similar, there is little difference in carrier injection from the carrier transport layer to the emission layer, which is the reason for the similar density and brightness of the two devices.

[0099] Figure 8 The external quantum efficiency curves of the PPF electroluminescent device doped with the product of Example 1-2 are shown in FIG.

[0100] like Figure 8 As shown, when the organic small molecule doping concentration is 30%, the EQEmax of the t-BuTPAniq organic light-emitting device and the tBu-TPA2niq organic light-emitting device are 4.0% and 3.6%, respectively.

[0101] Fig. 9 The electroluminescence spectra of the PPF electroluminescent device doped with the product of Example 1-2 are shown in Figure 1, where (a) is Example 1 and (b) is Example 2.

[0102] like Fig. 9 As shown, the two devices exhibit the same EL spectra and emit strongly in the blue region with the maximum emission band at 472 nm.

[0103] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A D-π-A type organic small molecule electroluminescent material, characterized in that: The general structural formula of the D-π-A type organic small molecule electroluminescent material is as follows: Wherein, X is The preparation method of the D-π-A type organic small molecule electroluminescent material comprises the following steps: Mix tBu-TPA and dibromonaphthalene and perform coupling reaction to obtain intermediate 1; The intermediate 1 is mixed with biboric acid pinacol ester, and subjected to borylation reaction to obtain the intermediate 2; The intermediate 2 and 1-bromoisoquinoline are mixed and subjected to a Suzuki coupling reaction to obtain the D-π-A type organic small molecule electroluminescent material; The structural formula of the tBu-TPA is shown below: The dibrominated naphthalene is 1,4-dibromonaphthalene or 2,6-dibromonaphthalene.

2. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The molar ratio of the tBu-TPA to the dibrominated naphthalene is 1.9-2:3.9-4.

3. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The coupling reaction was carried out at a temperature of 80° C., for a time of 6 h, in an oxygen-free atmosphere.

4. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The molar ratio of the intermediate 1 to the diboric acid pinacol ester is 2:

3.

5. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The temperature of the borylation reaction is 110° C., the time is 24 hours, and the atmosphere is an oxygen-free atmosphere.

6. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The molar ratio of the intermediate 2 to 1-bromoisoquinoline is 1-1.055:1.2-1.

27.

7. The D-π-A type organic small molecule electroluminescent material according to claim 1, characterized in that: The temperature of the Suzuki coupling reaction is 110° C., the time is 24 h, and the atmosphere is oxygen-free.

8. Use of the D-π-A type organic small molecule electroluminescent material according to claim 1 in preparing a light-emitting layer of an electroluminescent device.

9. A method for preparing a light-emitting layer of an electroluminescent device, characterized in that: Prepared by mixing the D-π-A type organic small molecule electroluminescent material according to claim 1 with a host material; The D-π-A type organic small molecule electroluminescent material accounts for 10-40 wt.% in the light-emitting layer of the electroluminescent device.

Citation Information

Patent Citations

  • Isoquinoline derivative compound and organic electroluminescent device using the same

    KR1020150138473A